2015
DOI: 10.3164/jcbn.14-92
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos and multi-walled carbon nanotubes generate distinct oxidative responses in inflammatory cells

Abstract: Asbestos exposure is considered a social burden by causing mesothelioma. Despite the use of synthetic materials, multi-walled carbon nanotubes (MWCNTs) are similar in dimension to asbestos and produce mesothelioma in animals. The role of inflammatory cells in mesothelial carcinogenesis remains unclear. Here, we evaluated the differences in inflammatory cell responses following exposure to these fibrous materials using a luminometer and L-012 (8-amino-5-chloro-7-phenylpyrido[3,4-d]pyridazine-1,4-(2H,3H) dione) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
0
21
1
1
Order By: Relevance
“…In particular, cellular DNA damage can result from direct interaction between CNTs and the genome, or indirectly via CNT-induced oxidative stress and inflammatory responses. Interestingly, at least for multi-walled CNTs, most of the ROS formation seems to result from cellular activation and an involvement of NADPH oxidase and superoxide radicals (Funahashi et al 2015). This is contrasting the results obtained with asbestos fibers, as do data that provide evidence that CNT fibers may also scavenging ROS to certain extents, an effect that actually should be inversely related to its genotoxicity (van Berlo et al 2012).…”
contrasting
confidence: 54%
“…In particular, cellular DNA damage can result from direct interaction between CNTs and the genome, or indirectly via CNT-induced oxidative stress and inflammatory responses. Interestingly, at least for multi-walled CNTs, most of the ROS formation seems to result from cellular activation and an involvement of NADPH oxidase and superoxide radicals (Funahashi et al 2015). This is contrasting the results obtained with asbestos fibers, as do data that provide evidence that CNT fibers may also scavenging ROS to certain extents, an effect that actually should be inversely related to its genotoxicity (van Berlo et al 2012).…”
contrasting
confidence: 54%
“…Hansen et al reported that the geometry and/or chemical composition of asbestos is important for the release of superoxide anions by leucocytes during frustrated phagocytosis [ 56 , 57 ]. Indeed, crocidolite and amosite induced significant ROS generation by neutrophils with a peak at 10 min, whereas that of chrysotile was ~25% of the crocidolite/amosite response [ 58 ].…”
Section: Chronic Inflammation Affects MM Developmentmentioning
confidence: 99%
“…Excess iron in the target cells was in common, which appears to have induced a common genetic alteration, homozygous deletion of p15 / p16 tumor suppressor genes. Early inflammatory responses by neutrophils were lacking for MWCNT …”
Section: Introductionmentioning
confidence: 99%